Sumo wrestling. - Unknown:::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a sumo match at Santa Anita, California Assembly Center with the referee in traditional costume. The contestants are wearing heavy canvas belts which are used to hold, throw or force the opponent out of the dirt ring.